High-performance spoof surface plasmon polariton waveguides and splitters based on Greek-cross fractal units. (3rd April 2020) - Ye, Longfang; Chen, Yao; Zhou, Jianliang; Feng, Hao; Zhang, Yong; Liu, Qing Huo
Abstract: In this paper, we introduce the fractal geometry into the spoof surface plasmon polariton (SSPP) waveguide and splitter design. We propose a novel SSPP waveguide consisting of periodic corrugated Greek-cross fractal units (GCFUs) connected to a microstrip line. The generation process of periodic corrugated GCFUs is described and the dispersion characteristics are studied. We find we can engineer the property of the waveguide at will by tuning the parameters of the GCFU. To validate the proposed design, a wideband lowpass filter based on double-sided DCFUs with ultra-sharp roll-offs is fabricated and tested. Based on this waveguide concept, we design a wideband Y-splitter including an SSPP waveguide with double-sided GCFUs and two SSPP waveguide branches with single-sided GCFUs. To improve isolations and reduce the reflections between output ports of the Y-splitter, a 100 Ω resistor is loaded in the middle of two symmetrical branches to construct Wilkinson splitter to equally and efficiently split the energy of the SSPPs into two parts. The simulated and measured results show that the SSPP splitter possesses excellent performance in a passband of 1.5–4.0 GHz with low insertion loss (S21, S31 > −4 dB), high reflection loss (S11, S22, S33 < −10 dB), and high isolation (S32 < −10 dB). This work may open up a new door for the development of various plasmonic integrated functional devices.